Antifungal Sensitivity Against Fungal Isolates From Bovine Mastitis - Sukumar , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
In vitro antifungal susceptibility of mould isolates showed that Clotrimazole was the drug of choice followed by Itraconazole, Ketoconazole and Pimaricin. Less sensitivity was shown against Amphotericin B and Nystatin. All the mould isolates showed resistance to Fluconazole and Griseofulvin.
Keywords: Bovine Mastitis; Antifungal drugs